Media Online Lokal dalam Menerapkan Jurnalisme Pariwisata (Studi Pada Media Online Lokal Bengkulu Ekspress) - Siti Maymunah; Lisa Ardhianti; Alfarabi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Tourism journalism is a journalism practice that aims to report on tourist destinations in an area, both for promotion and information. The development of online media in the country is increasingly rapid, making online media ideal as the first platform for searching for information about tourist destinations in a place as well as information on available facilities and infrastructure. Bengkulu Ekspress as a pioneer of online media in Bengkulu Province has some of which are about tourism. The aim of this research is to find out how tourism journalism is implemented on the Bengkulu Ekspress online media channel. This research uses a qualitative descriptive method which describes the results of observations seen from the research object using the framing analysis method. The results of this research explain that Bengkulu Ekspress implements tourism journalism by applying a special rubric entitled Bengkulu Tourism and Culinary Tourism and the locality of the news presented by Bengkulu Ekspress.com makes news about tourist destinations more specific to the Bengkulu Province area only. Apart from that, Bengkulu Ekspress also provides information about accommodation and transportation with narratives that attract readers to imagine their travel estimates in tourism journalism reporting.